102 Developing effective leaders: creating change champions in children's healthcare. (12th November 2018) - Parish, Emma; Runnacles, Jane; Davey, Nicola; Roueché, Alice
Abstract : Aim: Our aim is to equip those working with young people across healthcare in London with the skills and habits of an improver, enhance local services, and become role models for Quality Improvement (QI). Methods: The London School of Paediatrics (LSP) worked with QIClearn™ to deliver a blended learning programme. An initial pilot in 2017 showed that many attending lacked understanding of QI (35% stating they had never seen the QI Model for Improvement). Post-pilot feedback was positive (83% felt empowered that they can make changes within their workplace, 80% had taught someone else something about QI). Building on this feedback, in 2018, we delivered a 16 week course to 23 participants (18 trainees, 1 pharmacist, 1 consultant and 3 patient and carer learners), taking them through the Model for Improvement, measurement, human factors and presentation. A bespoke online social learning platform was developed. Participants worked through content with the support of a mentor, while carrying out QI projects in their workplace. Interactive modules, resources, forums and webinars were complemented by 2 full-day face-to-face workshops. We used QI methods to assess and improve the programme. Results: Initially 50% of participants stated it was the first time they had seen the Model of Improvement and only 1 in 5 had used it and felt confident. At the second workshop everyone had seen the Model and 50% had used it and felt confident. All participants who started the programme were awarded certificates of completion, 8 were recognised as Change Champions (showing highly improved knowledge and completion of a project to presentation), one of the attendees has been identified as a mentor-in-training for the next cohort. Further data is being collected on sustainable practice. Conclusion: This programme shows that blended learning with mentoring can support the professional development of emerging leaders within QI.